2002
DOI: 10.1177/107110070202300104
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Achilles Tendinosis: Surgical Treatment Through a Central Tendon Splitting Approach

Abstract: Twenty-two heels in 21 patients treated surgically for a primary diagnosis of insertional Achilles tendinosis were reviewed on the basis of preoperative and postoperative examinations, office records, and a comprehensive questionnaire administered to each subject. Each patient underwent surgical treatment using a midline-posterior skin incision combined with a central tendon splitting approach for debridement, retrocalcaneal bursectomy, and removal of the calcaneal bursal projection as necessary. The findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
191
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(197 citation statements)
references
References 25 publications
3
191
2
1
Order By: Relevance
“…26 Surgery is costly in terms of financial resources, time off work due to weight-bearing restrictions, and risk of complications. 15,24 Moreover, even a year after surgery, many patients continue to report some pain and functional limitations. 15,24 Despite the severity and chronicity of this problem, there is little research to guide the development of new physical therapy interventions for IAT.…”
mentioning
confidence: 99%
“…26 Surgery is costly in terms of financial resources, time off work due to weight-bearing restrictions, and risk of complications. 15,24 Moreover, even a year after surgery, many patients continue to report some pain and functional limitations. 15,24 Despite the severity and chronicity of this problem, there is little research to guide the development of new physical therapy interventions for IAT.…”
mentioning
confidence: 99%
“…Post operatively the patients were evaluated using ankle and foot scale. [10] The pre-operative score varied from 37 to 43 points with an average of 41 points and postoperatively the score varied from 81 to 83 points with an average of 82 points. Out of 25 patients 20 patients had complete relief of symptoms by three months.…”
Section: Materials and Methodmentioning
confidence: 99%
“…Mc Garvey et al reported improvement in 89% of their cases treated with conservative measures. 5 In patients where conservative methods fail, surgery may be indicated. Several methods have been described including excision of the retrocalcaneal bursa, calcaneal osteotomy, and calcaneal osteotomy with Achilles tendon debridement.…”
Section: Introductionmentioning
confidence: 99%